PILOT DECISIONS ARE THE RESULT OF MANAGEMENT DETERMINING FLIGHT SAFETY - I Gusti Bagus Mahendra Putra; Hery Winoto Tj; Soegeng Wahyoedi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Aviation safety is the ultimate goal of aviation in both civil and military in several accident reports and data from the aviation safety directorate of the Indonesian Army Aviation Center (Puspenerbad) human factors rank first cause of accidents as much as 74%. The purpose of this study is to determine the magnitude of the influence Flight Experience and Flight Proficiency against pilots decision making which has implications for aviation safety. The method in this study used quantitative descriptive analysis, with 99 respondents. Data collection is carried out by distributing questionnaires Google Forms and analyzed with the app SmartPLS 4.0. The conclusions obtained in this study put Flight Experience and Flight Proficiency does not affect flight safety if not mediated by the pilot decision making and flight safety is affected by pilots decision making.